Performance of pilot-scale constructed wetlands for secondary treatment of chromium-bearing tannery wastewaters - Dotro, Gabriela (2012)
Tannery operations consist of converting raw animal skins into leather through a series of complex water- and chemically-intensive batch processes. Even when conventional primary treatment is supplemented with chemicals, the wastewater requires some form of biological treatment to enable the safe disposal to the natural environment. Thus, there is a need for the adoption of low cost, reliable, and easy-to-operate alternative secondary treatment processes. This paper reports the findings of two pilot-scale wetlands for the secondary treatment of primary effluents from a full tannery operation in terms of resilience (i.e., ability to produce consistent effluent quality in spite of variable influent loads) and reliability (i.e., ability to cope with sporadic shock loads) when treating this hazardous effluent. Areal mass removal rates of 77.1 g COD/m2/d, 11 g TSS/m2/d, and 53 mg Cr/m2/d were achieved with a simple gravity-flow horizontal subsurface flow unit operating at hydraulic loading rates of as much as 10 cm/d. Based on the findings, a full-scale wetland was sized to treat all the effluent from the tannery requiring 68% more land than would have been assumed based on literature values. Constructed wetlands can offer treatment plant resilience for minimum operational input and reliable effluent quality when biologically treating primary effluents from tannery operations.